Nullpest: a mobile application of agricultural pest locator using sonar sensor set-up - Dan Michael A, Cortez; Charito M, Molina; Marmelo V., Abante; Myra S, Santos (International Journal of Engineering and Technology, 2018)
Philippines have already achieved its highest peak when it comes to substantive agricultural activities. The country has been one of the most leading distributors of agricultural crops most especially the rice commodity all throughout the world. With this, it can be concluded that agriculture is one important factor that affects the Philippines’ economy, thus, it must be given thorough attention and importance not only by the country’s government but also its constituents. There are inevitable factors that affects agricultural yield which results to rapid decrease of crop activities resulting to a devastating loss to the Philippine farmers, one of which is the existence of agricultural pest. These destructive pest gives fatal damage to agricultural crops by thriving its nutrients resulting to agricultural loss. Considering this, the aim of the study is to aid and help farmers locate such agricultural pest particularly on the rice commodity, give pesticide monitoring in order to limit pesticide usage that gives possible health risk to consumers, and lastly give pest information to its user particularly on farmers. With the combination of a Mobile Application and Arduino device all of this will become possible.